POSITIVISM AS A NEW ERA IN PHILOSOPHY AND ITS INFLUENCE ON ISLAMIC SOCIAL STUDIES - Nur Wakhidah; Alda Syafira (LP2M IAIN Sultan Amai Gorontalo, 2025)
The influence of positivism is reflected in efforts to integrate empirical methods with normative religious values, creating a dialectical relationship between scientific rationality and the spirituality of revelation. This study employs a qualitative method with a library research approach by analyzing classical and contemporary works on positivist philosophy, sociology of religion, and Islamic social thought. Primary sources include philosophical texts from Comte, Durkheim, and Weber, while secondary data are drawn from modern Islamic academic literature discussing the epistemology of social science, such as works by Al-Attas, Arkoun, and Fazlur Rahman. The analysis uses a descriptive-analytical approach to explore the relationship between positivism and Islamic social science paradigms, particularly in terms of epistemology, methodology, and research ethics. The findings indicate that positivism has significantly contributed to the rationalization of social studies in Islam, particularly in the fields of economics, politics, and education, by emphasizing the importance of observation and empirical data. However, adopting positivism in its entirety risks neglecting the transcendental dimension that lies at the core of Islamic teachings. Therefore, an integrative approach is needed, one that combines scientific objectivity with theological values so that Islamic social science maintains its spiritual identity. Thus, this article argues that positivism can serve as a methodological inspiration for the development of Islamic social studies, provided it operates within a tawhidic epistemological framework that balances rationality and moral spirituality.